PENINGKATAN PENGETAHUAN PENELITIAN TINDAKAN KELAS DALAM KAITANNYA DENGAN IDENTIFIKASI MASALAH PADA SISWA - Puri, V. G.S.; Wijaya, D.A. P.; Noveni, N. A.; Septiningsih, D. S. (Buletin Udayana Mengabdi, 2022)
Classroom Action Research is one of the ways to improve the quality of education. By doing Classroom Action Research, teachers are expected to be able to identify problems that can hinder learning activities, including the various circumstances and characteristics of students. This activity aims to 1) increase teacher’s knowledge about Classroom Action Research, 2) help educators understand the stages of adolescent development in order to identify problems in the classroom, 3) increase awareness about the importance of behavioral observation competence in the classroom so that educators are expected to be more sensitive in solving problems. The method used in this community service activity is lecture and question-answer. The results obtained from the training which were attended by 15 teachers of SMP Muhammadiyah 1 Purbalingga and SMP Muhammadiyah 2 Purwokerto were increased awareness of improving class quality through Classroom Action Research and a deeper understanding of the characteristics of adolescent students in order to get the right solution for solving problems that occur in the classroom. Participants gave a good response to this activity and hope it will be held again and also be held in other school.   Keywords: adolescent developmental stages, classroom action research, teacher